Impact of Soil test based Nutrient Management Technologies in Rice under KC Canal Command Area of Kurnool district of Andhra Pradesh - K. V.Ramanaiah,; G.Dhanalakshmi,; G.Rajender Reddy,; A.Krishna Murthy,; M.Sudhakar, (Journal of Agricultural Extension Management, 2013)
Frontline demonstrations were conducted from 2007 to 2011 in KC Canal. Command of Kurnool district, Andhra Pradesh to know the usefulness and · economic advantage of soil test based nutrient management technology in rice. Five villages were identified and 1O farmers in each of the selected villages were randomly chosen. At the beginning of the demonstrations a base ' line survey of selected farmers with respect to knowledge and adoption level of different nutrient management practices, rice productivity costs and productivity levels was carried out. The demonstration of nutrient management technologies covering seven nutrient management practices was .conducted in the selected farmers ' fields under close supervision of Krishi Vigyan Kendra for a period of five years. After five years, the impact of knowledge and adoption level of soil test based nutrient management technologies and productivity enhancement in rice were assessed. The results clearly indicate an improvement in knowledge level, adoption level among the selected farmers besides yield advantage and high net income over the existing practice of nutrient application